Topological optimization of wheel assembly components for all terrain vehicles. (2022) - Jasoliya, Dhruvin; Shah, Dhaval B.; Lakdawala, Absar M.
Abstract: The wheel assembly retains the wheel attached to the vehicle and allows turning movement. The wheel assembly of four-wheelers is located between the brake drums or brake discs and the drive axle. In this research paper, the topological optimization of various wheel assembly components of an all-terrain vehicle is carried out using Altair HyperWorks software. The main aim of carrying out topological optimization analysis is to reduce the weight and space used by the components. The need for weight reduction is to make lightweight components of the vehicle to attain high speed without compensation the strength. The steering and cornering responsiveness of the vehicle can be increased by reducing the weight of rotational wheel assembly components. The proper space and material distribution, as well as strength for the impact loads, is achieved during optimization. The design calculation for the wheel assembly components is carried out followed by CAD modeling using SolidWorks. The finite element analysis is performed as per impact loading and other boundary conditions. Around 60% weight reduction is achieved through topology optimization for various wheel assembly components like front and rear knuckles and hubs. The static structural analysis is further performed for the final design of wheel assembly components.